Rapid ammonia leak detection and alarm system using optical sensing technology - Hadi, Manap; Mohd Ashraf, Ahmad; Kamarul Hawari, Ghazali; Mohd Amir Shahlan, Mohd Aspar; Usman, Fahad (Elsevier, 2025)
Accidental leaks of high concentrations of ammonia pose significant risks including fatalities and severe injuries. In Malaysia, numerous incidents have been reported due to ammonia leakage and exposure. Therefore, an effective detection and warning systems is urgently needed. This paper reported a system than can trigger an alarm when ammonia gas was detected and reach certain concentration in the working area. The alarm system was equipped with a self-developed optical sensor which has excellent accuracy with an averaged error of 1.22 %, fast response and recovery time which are 3 s and 4 s respectively. The sensor also does not depend on the flowrate of the detected gas. The design includes optical fiber integration, allowing the placement of the detector and light source at safe locations. Additionally, a LabVIEW-based interface was developed to monitor and display real-time ammonia concentrations. This project successfully developed a system capable of detecting ammonia leakage and triggering an alarm within 3 sec.